Efeitos da intensidade do treinamento aer??bio sobre o comprimento do tel??mero e suas prote??nas de prote????o durante o envelhecimento - Cunha, Verusca Najara de Carvalho (2015)
Telomeres are composed of complex deoxyribonucleic acid and proteins located at the ends of chromosomes, formed by a short sequence of nitrogenous bases (5'-TTAGGGn -3 ') repeated several times. Are connected to a multiprotein complex called "shelterin" consists of six proteins (TRF1, TRF2, POT1, TIN2, RAP1 and TPP1) which maintains telomere homeostasis, preventing degradation. Telomeres are affected by the DNA polymerase inability fully replicate the tape 5' end of the chromosome. The results of such failure are successors shortenings with each cell division, which leads to extremely short telomeres at the end of cell division, resulting in cell senescence. Therefore telomeres are considered a potential biomarker of aging at the cellular level. The shortening of telomeres has been associated with an increased risk of developing age-related diseases such as diabetes, cardiovascular disease and obesity. In contrast, it is believed that physical exercise can attenuate the shortening rate of telomeres, even in the elderly. However, it is possible that there is a 'dose' ideal of physical exercise that can enhance this beneficial effect. The objective of this study was to analyze and compare the effects of aerobic training intensity swimming conducted in two intensity domains (high and low) on the expression of genes encoding the protective telomeric proteins (trf1 and trf2), associated proteins cellular senescence (p53 and Chek2), in addition to measuring telomere length in gastrocnemius and myocardium old mice. Sixteen animals were divided into four groups: two groups submitted to twelve weeks of physical training of swimming at low intensity (BI) and high intensity (AI) and two who remained sedentary for the same period, with a group of young animals (CONTj) and elderly animals (CONTi). Training consisted of swimming exercise three times a week, 20 minutes per session for the group AI and 40 minutes for BI with load corresponding to 3% body weight (%PC) (BI) and 6%PC (AI). An incremental test for functional evaluation was performed every four weeks to measure the maximum load (Gm??x). After the training period, animals were sacrificed for removal of tissue samples for analysis of genes expression related to telomeres. The results suggest that high intensity exercise is "teloprotetor" in the gastrocnemius tissue, since telomere length of the elderly animals did not differ from each other, however, the animals in this group (AI) had a lower expression of genes of proteins protective (trf1 and trf2) and cellular senescence (p53). These results suggest that the intensity at which the exercise is performed interfere with telomere length and that this response is tissue dependent, since the same results were not observed in cardiac tissue of animals.